Pengaruh Corporate Social Responsibility Disclosure pada Nilai Perusahaan dengan Kepemilikan Asing Sebagai Variabel Pemoderasi - Teja Permana, Ida Bagus; Wirawati, Ni Gusti Putu (E-Jurnal Akuntansi; Vol 25 No 1 (2018), 2018)
Efforts to increase the value of companies in the utilization of existing resources are often not balanced by maintaining the sustainability of existing sources. The development of companies can cause damage to the surrounding environment. Therefore arises awareness to reduce the negative impact caused by the company. Awareness to reduce the negative impact is Corporate-Social Responsibility. The purpose of this study to determine the effect of Corporate Social Responsibility disclosure on the value of companies with foreign ownership as a moderator variable. The method used in this research is nonprobability sampling method that is purposive sampling. Data analysis techniques used to test the hypothesis in this study is Moderated Regression Analysis (MRA). The results of this study indicate that CSR Disclosure has a positive effect on firm value. The results of this study also show that foreign ownership strengthens the disclosure relationship of CSR to firm value. Keywords : Corporate social responsibility disclosure, foreign ownership, corporate value